2021
DOI: 10.1021/acsomega.0c05599
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Human Bitter Taste Receptor Response to Sesquiterpene Lactones from Edible Asteraceae Species and Suppression of Bitterness through pH Control

Abstract: Vegetables are important sources of nutrients and bioactive compounds; however, their consumption is often insufficient, partly because of unpleasant taste characteristics. This study aimed to investigate the mechanisms underlying bitter taste reception and to develop methods to suppress bitterness. We focused on sesquiterpene lactones found in edible Asteraceae species. HEK293T cells that heterologously expressed human bitter taste receptors (including TAS2R46) together with a chimeric G protein were analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…In the present study the TAS2R activation profile of bitter compounds from chicory and chicory-based surrogate coffee were analyzed and responses of three human bitter taste receptors, the TAS2R43, the TAS2R46 and, to a lesser degree, the TAS2R14, were observed. A previous publication investigating a similar set of four sesquiterpene lactones from edible Asteraceae species reported the activation of TAS2R46, thus confirming part of our study, however, activation of TAS2R14 and TAS2R43 was not observed (26). Whereas the previous study reported 10.3389/fnut.2022.1082698 a threshold concentration of about 1 µM for lactucopicrin and an extrapolated EC 50 -concentration of 16.6 µM for the TAS2R46, our data demonstrated a 30-50-fold higher sensitivity for lactucopicrin for the same receptor.…”
Section: Identification Of Tas2rs Responsive To Chicory Bitter Substa...supporting
confidence: 92%
“…In the present study the TAS2R activation profile of bitter compounds from chicory and chicory-based surrogate coffee were analyzed and responses of three human bitter taste receptors, the TAS2R43, the TAS2R46 and, to a lesser degree, the TAS2R14, were observed. A previous publication investigating a similar set of four sesquiterpene lactones from edible Asteraceae species reported the activation of TAS2R46, thus confirming part of our study, however, activation of TAS2R14 and TAS2R43 was not observed (26). Whereas the previous study reported 10.3389/fnut.2022.1082698 a threshold concentration of about 1 µM for lactucopicrin and an extrapolated EC 50 -concentration of 16.6 µM for the TAS2R46, our data demonstrated a 30-50-fold higher sensitivity for lactucopicrin for the same receptor.…”
Section: Identification Of Tas2rs Responsive To Chicory Bitter Substa...supporting
confidence: 92%
“…Most of the reported species were bitter Asteraceae (members of 14 genera) and pungent/bitter Brassicaceae (3 genera). Among other bitter compounds, edible Asteraceae contain sesquiterpenoids, which are considered to be chemosystematic markers of them [ 76 , 77 ], while Brassicaceae contain glucosinolates (bitter) and precursors of isothiocyanates (pungent), generally making these plants both bitter and pungent [ 78 ].…”
Section: Resultsmentioning
confidence: 99%
“…An example of the role that different culinary practices could have in the sensory acceptability of a wild plant comes from a study demonstrating how the perception of the bitter sesquiterpene lactones compounds in Asteraceae is different at different pH levels: it is enough to add lemon to a plant of this family to mitigate the bitterness of these compounds (also proven by in vitro tests) [ 76 ], making it more acceptable. However, in the intestine, the pH is different (less acidic), and, therefore, the activation of bitter receptors expressed there will be possible, with all the associated health benefits.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, FH06 before fermentation has obvious bitterness in the senses, but the bitterness disappears after fermentation. Studies have found that the bitter taste of Compositae plants can be reduced by adjusting the pH value to acidity [ 43 ]. In this study, it may be that fermentation produced organic acids, which lowered the pH of the beverage and masked the bitter taste.…”
Section: Resultsmentioning
confidence: 99%